A SYSTEMATIC REVIEW OF MATERNAL CALCIUM SUPPLEMENTATION AND PAEDIATRIC HEALTH. (16th June 2015) - AL DORAZI, SHOROK ALI; AL TALALWAH, WASEEM
Abstract : Calcium is an important element of body composition 1, 2 as well as normal physiological functions 3 . A neonate's body has around 20–30 g calcium present at birth 2, 4 –6 and this amount has to be supplied by the mother since human body cannot synthesise calcium 2 . Therefore, if the mother has a shortage of calcium, the foetus might be affected.